Improving Gender Equality and Rural Livelihoods in Senegal through Sustainable and Participatory Energy Management : Senegal's PROGEDE II Project - Hammond, Alicia (World Bank, Washington, DC, 2015)
Launched in 2011, the Second Sustainable and Participatory Energy Management Project (PROGEDE II) for Senegal has been hailed for effectively mainstreaming a gender perspective into an energy project. Under the project, women have participated more in decision making; developed skills in technical production, entrepreneurship, and organizational management; and benefitted from increased incomes.